Bio-deterioration of papers with special reference to National Library of Sri Lanka - Gangabadaarachchi, R. V. (My University, 2009)
Bio deterioration of papers with special reference to National Library was investigated. Deterioration of library materials is a major problem in the National Library. As it is the responsibility of National Library to preserve and conserve the cultural heritage at present for the future generations, deteriorative factors to the collection should be identified. In this study, causes for bio-deterioration was identified and tested the effectiveness of Neem extract (which was prepared by the Department of National Archives) on fungi present on papers. A survey was done to identify the presence of insects, fungi and damages to the collections using stratified random samples. 378 samples of all 3 stack areas of the National Library were investigated. Silverfish, Book worm and fungi infestations were identified in the collection. It was noted that old books as well as newly acquired books were also affected by insects and the percentage of the damages to the collection stored in the second floor was high compared to other stack areas.